Computational investigation on protein sequence of non-O157 VTEC for potentiality of vaccine production - Karim Khan, Md Fazlul; Kabir, M. Nomani; Rashid, Shah Samiur; Tayan, Omar; Mohammad Nazmul Hasan, Maziz (IEEE, 2020)
Computational method can be used for investigation of the protein sequences for developing a vaccine against infections. In this present study, a protein derived from non-O157 Verotoxin-producing E. coli (VTEC) was identified as a potential vaccine candidate that can be used to evaluate their immunogenicity and protective capability against VTEC infections. Identification of potential B-cell epitopes for promising vaccine was carried out by evaluating the protein derived from non-O157 VTEC with the methods of beta turns, hydropathicity, surface accessibility and antigenicity. The methods were implemented in MATLAB. Our test results demonstrated that the VTEC-derived protein has plausible characteristics which provide significant insights for further investigations and will assist in finding potential drug targets/vaccine candidates.